CORONARY STENT AND PROSTHETIC HEART VALVE INFORMATION VIA SMARTPHONE NEW APPLICATIONS IMPROVING HEALTH-CARE QUALITY OF PATIENTS HAVING UNDERGONE PERCUTANEOUS CORONARY INTERVENTION AND ARTIFICIAL VALVE REPLACEMENT - Imagawa, Hiroshi; Yagi Takayoshi, .; Taniguchi, Hirokatsu (MATTER: International Journal of Science and Technology, 2017)
There are a huge number of patients who have been treated by percutaneous coronary intervention (PCI) with stenting. Many studies have reported that cessation of antiplatelet medications produces in-stent thrombosis in patients, especially those with drug-eluting stent. Also, patients with mechanical prosthetic valves must not stop the anticoagulant therapy even in the late postoperative period, irrespective of type of the valve or position in the heart. However some people voluntarily abandon taking the antiplatelet or the anticoagulant medicines when they encounter an unexpected emergent medical problem. We have made a hypothesis that smartphone based ubiquitous system of recording coronary stent information and prosthetic heart valve data would be useful in managing patients, who underwent PCI or artificial heart valve surgery. We developed smartphone applications archiving PCI and prosthetic heart valve data, “Coronary Stent Information” and “Prosthetic Heart Valve Information”, respectively. These simple and free applications run on iOS or Android. More than eighty percent of participants approved one of these applications. We concluded that coronary stent and prosthetic heart valve data recording systems using smartphone technology are simple and valuable methods in managing people suffering from ischemic or valvular heart disease. These ubiquitous applications would improve health-care quality of patients who have undergone PCI and prosthetic heart valve surgery.